THERMAL ANALYSIS OF DIFFERENT REFUSE DERIVED FUELS SAMPLES - Ayas, Gizem; Öztop, Hakan Fehmi (Vinca Inst Nuclear Sci, 2021)
As a result of the activities carried out by people to maintain their daily lives in different places such as homes, hospitals, hotels or workplaces, waste consisting of furniture, paint, batteries, food waste, sachets, bottles, fabrics, and fibers with the heterogeneous structure is called municipal solid waste. Secondary fuels with higher heating value, which are generated by recycling of non-recyclable and reusable wastes in municipal solid wastes, are called as refuse derived fuel (RDF). In this study, RDF1 (taken in December, winter season) and RDF2 (taken in June, summer season) samples obtained from different dates were used. The ultimate, proximate, calorific value, X-ray fluorescence, thermogravimetric analysis, and differential scanning calorimetry analysis were performed for these samples. Combustion characterization from RDF samples was investigated in the applied analyzes. The results of the content analysis made were examined separately and compared with the thermogravimetric analysis and differential thermal analysis combustion graph curves. It was revealed that the RDF1 sample had a better combustion compared to the RDF2 sample, as the ash amount and content obtained as a result of the combustion also supported other data. In addition, the results of the analysis show how different the RDF samples taken from the same region in two different months are different from each other.
Keywords: municipal solid waste; RDF; thermal analysis; fuel; differential scanning calorimetry